Influencia del tiempo de exposición, concentración de semiconductor y concentración de pigmento activador en celdas fotovoltáicas a base de beta vulgaris (betarraga). - Ramos Soroa, Luis Jesús (2014)
The purpose of this research was to evaluate the performance of photovoltaic cells based on Betanina as the active material (Beta vulgaris pigment or "Beet") in the generation of electricity, to changes in pigment activator concentration, concentration of semiconductor and time exposure to solar radiation. The results show that due to the configuration under which the photovoltaic cells based on Beta vulgaris (Beet) were developed, the amount of activator pigment does not significantly influence in the amount of voltage generated; being the main factors the amount of solar radiation and the concentration of semiconductor (ZnO). The thickness of the semiconductor layer (ZnO) proportionally effects on the amount of voltage generated by photovoltaic cells based on Beta vulgaris (Beet), however this behavior is maintained up to a semiconductor concentration of 0.077 gZnO/cell (at which the highest values of voltage is reached ) after which the amount of generated voltage decreases with the increased concentration of semiconductor. The amount of voltage generated by photovoltaic cells based on Beta vulgaris (Beet) is proportional to the amount of solar radiation received, registering a higher amount of voltage in the cells exposed to direct sunlight than in cells exposed to diffuse radiation solar. Finally, it was noted that higher values of voltage were registered around the second week of exposure to sunlight, after which they fall to a constant rate until the end of the measurement. From the data obtained in this investigation, it can be concluded that the photovoltaic cells based on Beta vulgaris (Beet), could represent an interesting alternative for the generation of electricity from sunlight.